"Why Some and Not Others?" The Determinants of the Quality and Prestige of Public Graduate Research Universities. (March 2014) - Hill, Kim Quaile; Capers, K. Jurée; Flink, Carla
Abstract: We offer the first systematic assessment of the factors thought to account for the quality and prestige of public research universities in the United States. We take account, too, of those potential causal factors identified in both contemporary and early descriptive research on these institutions. Our findings indicate that attributes of universities and their states from the first half of the twentieth century as well as some of their contemporary attributes are powerful predictors of their success in National Research Council peer evaluations of their research programs. The results provide a foundation for efforts to account systematically for the research achievements of these universities and evidence on state public policy influences on those research achievements.